The Role of Core Biopsy versus Vacuum-Assisted Breast Biopsy In Primary Breast Angiosarcoma. (29th July 2021) - Abate, Anna; Querques, Giulia; Giovanazzi, Riccardo; Di Bella, Camillo; Besostri, Valeria; Gisabella, Mara; Maino, Cesare; Ippolito, Davide; Corso, Rocco
Abstract : We report the case of a 45-year-old woman with a slow-growing palpable nodule on the left breast, confirmed as a well-defined opacity on mammography, corresponding to a 5 cm hyperechoic lesion on ultrasound, and considered, on the basis of clinical examination and radiological findings, to be consistent with a lipoma. One year later, the patient represented with an enlarged left breast mass and underwent further imaging investigation with subsequent diagnosis of primary breast angiosarcoma obtained via a Vacuum-Assisted Breast Biopsy. The patient developed metastatic disease and succumbed to the disease one year after definitive diagnosis. Primary breast angiosarcoma is a rare malignant vascular neoplasia, characterized by aggressive patterns, poor prognosis, and absence of pathognomonic radiological features. Currently, there are no evidence-based guidelines regarding treatment, even though wide surgical resection followed by chemo- and radiotherapy appears to improve survival.